2022
DOI: 10.3389/fendo.2022.959396
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of an estrogen receptor-regulated gene by first generation progestins requires both the progesterone receptor and estrogen receptor alpha

Abstract: Progestins, synthetic compounds designed to mimic the activity of natural progesterone (P 4 ), are used globally in menopausal hormone therapy. Although the older progestins medroxyprogesterone acetate (MPA) and norethisterone (NET) have been implicated in increased breast cancer risk, little is known regarding newer progestins, and no significant risk has been associated with P 4 . Considering that breast cancer is the leading cause of mortality in women, establishing which progestins increase breast cancer i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
2
2
0
Order By: Relevance
“…This finding remained significant even after accounting for other key prognostic factors such as lymph node status, tumour size, tumour grade and oestrogen receptor status. These results align with previous research [ 31 35 ].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding remained significant even after accounting for other key prognostic factors such as lymph node status, tumour size, tumour grade and oestrogen receptor status. These results align with previous research [ 31 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…Cathepsin D-negative patients have significantly better BCSS and less risk of either recurrence or metastasis than Cathepsin D-positive patients within this ER+ patient group. Other studies have reported similar findings [ 11 , 31 ]. While some studies found no association between Cathepsin D expression and ER status, their conclusions may be limited by their small sample sizes and reliance on ELISA for cytosolic Cathepsin D measurement [ 25 , 32 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With fewer AEs and more benefits in better sexual life, skin condition and physical activity, alternative therapies receives more and more attention [29]. Compared with, medroxyprogesterone acetate (MPA) and norethisterone (NET) which increased breast cancer risk, evidence suggests a differential effect of MHT containing E2 or natural progesterone (P4) and those containing CEE or progestins, with some evidence trending to a potentially better safety profile with E2 and/or P4 [30][31][32]…”
Section: Menopausal Hormone Therapymentioning
confidence: 99%